2010
DOI: 10.1111/j.1741-3737.2010.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Older Parent–Child Relationships in Six Developed Nations: Comparisons at the Intersection of Affection and Conflict

Abstract: Intergenerational solidarity and ambivalence paradigms suggest that emotional relationships between generations consist of both positive and negative sentiments. We applied latent class analysis to measures of affection and conflict in 2,698 older parent – child relationships in 6 developed nations: England, Germany, Israel, Norway, Spain, and the United States (Southern California). The best fitting model consisted of 4 latent classes distributed differently across nations but with a cross-nationally invarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 53 publications
11
130
1
5
Order By: Relevance
“…For their part, the S-DSI Emotional Cutoff and Emotional Reactivity subscales showed strong cross-cultural relevance, enabling the original DSI subscales to remain largely intact. Other research with a Spanish sample has shown that good intergenerational relationships (Rodrigo et al, 2004) are crucial for psychological adjustment and healthy life style, thus the costs associated with emotional cutoff may be especially high in a collectivist Spanish culture (Rodríguez-González & Cagigal de Gregorio, 2009;Silverstein et. al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For their part, the S-DSI Emotional Cutoff and Emotional Reactivity subscales showed strong cross-cultural relevance, enabling the original DSI subscales to remain largely intact. Other research with a Spanish sample has shown that good intergenerational relationships (Rodrigo et al, 2004) are crucial for psychological adjustment and healthy life style, thus the costs associated with emotional cutoff may be especially high in a collectivist Spanish culture (Rodríguez-González & Cagigal de Gregorio, 2009;Silverstein et. al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural norms regarding physical proximity and optimal personal space in the context of interactions dictate greater separation in physical space, expectations of greater independence in one's children, and greater focus on the nuclear rather than extended family network in U.S. as compared to Spanish populations (Georgas, Berry, Von de Vijver, Kagitcibasi & Poortinga, 2006;Schmitt et al, 2004). Maintaining a family orientation is more prominent in Spanish and other Mediterranean cultures from Southern Europe, relative to cultural traditions of Northern European countries (Alonso-Arbiol, Balluerka, Shaver, & Gillath, 2008;Silverstein, Gans, Lowenstein, Giarrusso & Bengtson, 2010;Schmitt et al, 2004). Few studies have explored whether these cultural differences are independent of or reflected in measures of psychological constructs such as differentiation of self.…”
Section: Introductionmentioning
confidence: 99%
“…It is customary to use dichotomous variables in latent class analyses of intergenerational relationships (Dykstra and Fokkema 2011;Hogan, Eggebeen and Clogg 1993;Silverstein and Bengtson 1997;Silverstein et al 2010). Though dichotomization suggests a loss of information, it ensures having a manageable number of cells for the latent class analyses.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Although Bengtson's solidarity paradigm has been defined as the 'gold standard' for assessing intergenerational relationships (Silverstein et al, 2010(Silverstein et al, , p. 1007, other investigators have developed broader or more detailed categories of informal helping behaviors between generations. Weiss (1974), for example, suggests a broad conception of six provisions in social relationships: attachment, social integration, opportunity for nurturance, reassurance of worth, a sense of reliable alliance, and obtaining guidance.…”
Section: Solidarity Conflict and Ambivalencementioning
confidence: 99%